Enhanced MiR-711 transcription by PPARγ induces endoplasmic reticulum stress-mediated apoptosis targeting calnexin in rat cardiomyocytes after myocardial infarction. (May 2018) - Zhao, Na; Mi, Lan; Zhang, Xunjun; Xu, Minyao; Yu, Haiyi; Liu, Zhongwei; Liu, Xiaojun; Guan, Gongchang; Gao, Wei; Wang, Junkui
Abstract: MicroRNA 711 (miR-711) levels in the heart change dynamically after myocardial infarction (MI). As peroxisome proliferator-activated receptor gamma (PPARγ) can upregulate miR-711 in adipocytes and cardiac fibroblasts, this study examined the precise mechanism of PPARγ-mediated miR-711 upregulation and its role in the heart in the early stages after MI. In a rat model of MI induced by left anterior descending coronary artery ligation, immunohistochemical and western blot analyses revealed increased PPARγ expression in cardiomyocyte nuclei after MI. PPARγ modulated miR-711 levels in neonatal rat cardiomyocytes, and chromatin immunoprecipitation and luciferase assays revealed that it bound the premiR-711 promoter to upregulate miR-711. Bioinformatics analysis identified calnexin as a putative miR-711 target; this was confirmed by luciferase, western blot, and real-time polymerase chain reaction analyses. Additionally, the transfection of a miR-711 mimic into cardiomyocytes induced the endoplasmic reticulum (ER) stress-induced apoptosis response by upregulating glucose-regulated protein 78 (GRP78), activating transcription factor (ATF6), spliced X-box binding protein 1 (XBP1), apoptotic signal-regulating kinase 1 (ASK1), CCAAT-enhancer binding protein homologous protein (CHOP), caspase-12, and endoplasmic reticulum oxidoreductase 1 alpha (ERO1a). Similarly, on day 2 after MI, increased miR-711 levels in the heart were accompanied by increased cardiomyocyte apoptosis, decreased calnexin levels, and increased levels of GRP78, ATF6, spliced XBP1, ASK1, CHOP, and caspase-12, as well as cardiomyocytes apoptosis. The mechanism underlying these effects may involve the direct binding of PPARγ to the pre-miR-711 promoter for the upregulation of miR-711, which may induce ER stress-mediated cardiomyocyte apoptosis via calnexin. These findings augment the general knowledge of the post-MI pathological process and suggest a therapeutic strategy for cardiac remodelling in the early stages after MI. Highlights: PPARγ promotes miR-711 expression by binding to the pre-miR-711 promoter after MI. MiR-711 binds to 3′ UTR of calnexin mRNA to down-regulate its expression. PPARγ-miR-711-calnexin pathway is involved in ER stress induced apoptosis after MI.